"More Like a Swagman than a Parliamentary Candidate": Federal Election Meetings in Rural New South Wales and Victoria, 1910–22. (1st May 2018) - Monnox, Chris
Abstract : Public meetings were one of the key electioneering methods employed in early twentieth-century Australia. These meetings and the beliefs that surrounded them did much to shape the era's broader approach to electioneering. Rural candidates embarked on extensive tours of their constituencies, reinforcing a political culture focused on local representatives. Wide-ranging networks of party supporters were required to organise and publicise these tours, and so the public meeting also helped sustain a need for large party memberships. Meetings could be used to target some voter groups, but the time-consuming character of candidates' tours meant that this potential was not often fully realised in the country.